Trace fossil analysis in a Paleogene braided river system from the Volta Redonda Basin, Continental Rift of Southeastern Brazil - Sedorko, Daniel; West, Daniel Carvalho; Nascimento, Diego Luciano [UNESP]; Mello, Claudio Limeira; Ramos, Renato Rodriguez Cabral; Ramos, Kimberly Silva; Scheffler, Sandro Marcelo (Taylor & Francis, 2025)
Trace fossils serve as valuable indicators for palaeoecological and paleoenvironmental research, recording organism behaviour influenced by environmental parameters. Trace fossils within braided river systems, however, have been rarely investigated. In addition, despite the growing interest in ichnological studies within the Continental Rift of Southeastern Brazil (CRSB), there remains a notable scarcity of research focusing on integrated ichno-sedimentological analysis including aspects of both trace fossils and their sedimentological context. This study analyzes and interprets ichnological data derived from two subsurface logs from the Paleogene Volta Redonda Basin. Core samples were examined for sedimentary facies, revealing four facies within the Resende Formation, related to unidirectional tractive flows and overbank deposits of a braided depositional paleoenvironment. The ichnocoenoses included Skolithos, and Beaconites. The results indicate that the Volta Redonda Basin experienced diverse depositional conditions characterized by dominant high-energy levels, while the presence of rhizohaloes in low-energy deposits suggests relative short periods of subaerial exposure. The dominance of Skolithos ichnofacies in the few bioturbated levels suggests that high-energy conditions were a barrier to intense colonization of the channels, while sparse signatures of Scoyenia ichnofacies characterizes colonization in desiccated overbank deposits.
Keywords: Beaconites; crustacean burrow; Rhizohaloes; Rift Basin; Taenidium